2016
DOI: 10.18632/oncotarget.8142
|View full text |Cite
|
Sign up to set email alerts
|

Difference in characteristics and outcomes between medullary breast carcinoma and invasive ductal carcinoma: a population based study from SEER 18 database

Abstract: Medullary breast carcinoma (MBC) is a unique histological subtype of breast cancer. Our study was designed to identify difference in characteristics and outcomes between MBC and invasive ductal carcinoma (IDC), and further confirm the prognostic factors of MBC. Utilizing Surveillance, Epidemiology, and End Results (SEER), we identified 84,764 eligible patients, including 309 MBC and 84,455 IDC. Compared with the IDC group, the MBC group was associated with younger age at diagnosis, higher grade, more advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…This result is in accordance with the observations of many authors who emphasis that patients with this advanced stage of the disease clearly predominate in percentage terms [2,10,18,21,22,24,25,[28][29][30]. According to certain authors, patients with stages I and II° of the disease represent more than 90% of the total.…”
Section: Stage Of Diseasesupporting
confidence: 91%
See 2 more Smart Citations
“…This result is in accordance with the observations of many authors who emphasis that patients with this advanced stage of the disease clearly predominate in percentage terms [2,10,18,21,22,24,25,[28][29][30]. According to certain authors, patients with stages I and II° of the disease represent more than 90% of the total.…”
Section: Stage Of Diseasesupporting
confidence: 91%
“…Similar population, microscopic and clinical characteristics, as well as immunohistochemically studied factors can be found quite often in the literature, obviously in varying frequency and intensity [1,2,15,17,18,[21][22][23][24][25][26][27][28][29][30]. However, it is important to stress that making strict comparisons between the present study group of patients and groups presented by other authors is very difficult and remains a questionable approach, since a T-MBC diagnosis itself is problematic and controversial.…”
Section: Clinicopathologic Characteristicsmentioning
confidence: 61%
See 1 more Smart Citation
“…Hormone receptor expression varies across the different histological types [21]. Utilizing Surveillance, Epidemiology, and End Results, a recent analysis demonstrated that the majority of invasive ductal carcinoma not otherwise specified was hormone receptorpositive but HER2 negative, while the majority of medullary carcinoma was triple negative [22]. Out of the patients in this study with small cell carcinoma of the breast; 31 % expressed ER, 13 % expressed PR, and 16 % expressed AR.…”
Section: Discussionmentioning
confidence: 63%
“…Incidentally, the literature also revealed the trend towards comparing MBC and invasive ductal carcinoma (IDC). Thus, from Korea [12], India [13] and China [14], there have been decisive comparisons. For instance, the last named authors were emphatic concerning the "Difference in characteristics and outcomes between medullary breast carcinoma and invasive ductal carcinoma.…”
Section: Introductionmentioning
confidence: 99%